Effects of replacing fishmeal with soybean meal on growth performance, liver antioxidant capacity and intestinal health in juvenile Asian red-tailed catfish (Hemibagrus wyckioides) - Weijia Cai; Xinping Li; Minglang Cai; Zhe Tang; Bo Zhu; Mengxi Yang; Yi Hu; Jihong Dai (Aquaculture Reports)
The present study was to evaluate the effects of different levels of soybean meal (SBM) substitute for fish meal (FM) on the growth performance, antioxidant capacities, and intestine health of Asian red-tailed catfish, Hemibagrus wyckioides. Five isonitrogenous and isolipidic diets were prepared: the FM diets contained 50 % fish meal, based on which four SBM diets were formulated as substitutes for 15 %, 30 %, 45 % and 60 % FM in the FM group diets, namely SBM15, SBM30, SBM45, and SBM60. Compared with the FM group, the SBM45 and SBM60 groups exhibited significantly elevated serum glutamate pyruvate transaminase (GPT) levels and showed evidence of liver oxidative stress injury. Concurrently, there were decreases in triglyceride (TG) and total cholesterol (TC) levels (P < 0.05). Besides, hepatic antioxidant enzyme activities and nrf2 gene expression levels were markedly upregulated in the SBM45 and SBM60 groups (P < 0.05). In the SBM45 and SBM60 groups, the lamina propria of the intestinal villi became wider, and the number of goblet cells increased. The tight junction proteins zo-1, claudin-4 and occludin were significantly downregulated in the SBM45 and SBM60 groups. At the same time, the pro-inflammatory factors inos, tgf-β, tnf-α and il-1β were significantly upregulated in these two groups (P < 0.05). The SBM45 and SBM60 diets contributed to significant alterations in the intestinal microbiota. In the SBM60 group, the relative abundances of Cetobacterium and Lawsonia significantly increased, and the intestinal microbiota function was predicted to undergo upregulation of complex carbohydrate metabolism and fermentation. The results of the broken-line regression analysis for FCR and SGR indicate that the optimal substitution level of FM with SBM for H. wyckioides feed is estimated to be 36.83 %-37.31 %. Substitution levels exceeding this range, such as 45 % and 60 %, adversely affect liver and intestinal health.